Antioxidant enzyme activity and malondialdehyde levels can be modulated by Piper betle, tocotrienol rich fraction and Chlorella vulgaris in aging C57BL/6 mice - Nor Syahida Aliahmat; Mohd Razman Mohd Noor; Wan Junizam Wan Yusof; Suzana Makpol; Wan Zurinah Wan Ngah; Yasmin Anum Mohd Yusof (Clinics, 2012)
OBJECTIVE: The aim of this study was to determine the erythrocyte antioxidant enzyme activity and the superoxide dismutase, catalase, glutathione peroxidase, and plasma malondialdehyde levels in aging mice and to evaluate how these measures are modulated by potential antioxidants, including the tocotrienol-rich fraction, Piper betle, and Chlorella vulgaris. METHOD: One hundred and twenty male C57BL/6 inbred mice were divided into three age groups: young (6 months old), middle-aged (12 months old), and old (18 months old). Each age group consisted of two control groups (distilled water and olive oil) and three treatment groups: Piper betle (50 mg/kg body weight), tocotrienol-rich fraction (30 mg/kg), and Chlorella vulgaris (50 mg/kg). The duration of treatment for all three age groups was two months. Blood was withdrawn from the orbital sinus to determine the antioxidant enzyme activity and the malondialdehyde level. RESULTS: Piper betle increased the activities of catalase, glutathione peroxidase, and superoxide dismutase in the young, middle, and old age groups, respectively, when compared to control. The tocotrienol-rich fraction decreased the superoxide dismutase activity in the middle and the old age groups but had no effect on catalase or glutathione peroxidase activity for all age groups. Chlorella vulgaris had no effect on superoxide dismutase activity for all age groups but increased glutathione peroxidase and decreased catalase activity in the middle and the young age groups, respectively. Chlorella vulgaris reduced lipid peroxidation (malondialdehyde levels) in all age groups, but no significant changes were observed with the tocotrienol-rich fraction and the Piper betle treatments. CONCLUSION: We found equivocal age-related changes in erythrocyte antioxidant enzyme activity when mice were treated with Piper betle, the tocotrienol-rich fraction, and Chlorella vulgaris. However, Piper betle treatment showed increased antioxidant enzymes activity during aging.